Primary adrenal extranodal NK/T-cell lymphoma: A case report and literature review. (2020) - Ichikawa, Satoshi; Saito, Kei; Fukuhara, Noriko; Yokoyama, Hisayuki; Onodera, Koichi; Onishi, Yasushi; Ichinohasama, Ryo; Harigae, Hideo
Abstract: A 37-year-old man was admitted to our department following the detection of bulky tumors in his bilateral adrenal glands. A biopsy resulted in the diagnosis of extranodal NK/T cell lymphoma, nasal type (ENKL). After debulking by chemotherapy, allogeneic hematopoietic stem cell transplantation (alloHCT) was performed. Relapses in the liver and adrenal glands were identified 2 months post alloHCT, for which temporary administration of l -asparaginase resulted in complete metabolic response. However, multiple relapses in the central nervous system and lethal lymphomatous meningitis successively developed. Primary adrenal ENKL could tend to present as bulky lesion and follow an aggressive clinical course.